(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
Cashew is an important tree crop with huge export potential and economic benefits. Seed propagation is a major problem because it takes the crop a much longer time to reach edible maturity compared to vegetative propagation. In addition, true-to-type plants cannot be assured through seed propagation. This experiment was conducted to determine the effects of different concentrations of IBA and three scion types on the graft success of cashews. The experimental design for the study was 4 x 3 factorial arrangements in a Randomized Complete Block Design (RCBD) with three replications. The first factor was IBA at four different concentrations (0 ml, 750 ml, 1000 ml, and 1250 ml). The second factor was scion types at three levels (soft, semi-hard, and hardwood, respectively). Semi-hardwood cuttings treated with 1250 ml concentration of IBA took shorter days (13 days) to achieve graft success and had the highest percentage graft-take. For all the vegetative parameters studied (plant height, stem girth, number of leaves, root biomass and root length), semi-hardwood cuttings which were treated with 1250 ml concentration of IBA gave the best recordings and also had the highest percentage of survived seedlings after transplanting. In conclusion, for a successful graft success coupled with the corresponding growth of the seedlings, it is best to use 1250 ml of IBA concentration with semi-hardwood scion. Int. J. Agril. Res. Innov. Tech. 14(2): 132-145, December 2024